Phytosociological survey of weed plants in soybean culture in the Gurguéia Valley - Lopes, Camile Carvalho; Fontes, Larissa de Oliveira; Lazzarini, Luiz Eduardo Santos; Freitas, Francisco Claudio Lopes de; Costa Filho, José Hamilton da; Sousa, Eudinete Ribeiro de (Scientia Agraria Paranaensis, 2021)
Phytosociology is a set of ecological assessment methods that aim to provide a view of plant species distributions within a plant assemblage. The objective of the current study was to identify and quantify the plants designated as weeds in a glyphosate-resistant soybean crop, using a phytosociological survey of a conventional planting system on the Fazenda Agrosantos (09°27’4124.4” S and 45º01’00.4” O), Vale do Gurguéia, Monte Alegre municipality Piauí state, Brazil. The site lies at a mean altitude of 652 m. Field collections were made 15 days after initial soya planting. For sampling, a 0.40 x 0.40 m quadrat was used, thrown randomly twenty times within the experimental area. Weeds were identified and quantified using the sum of the samples obtained from the quadrat samples. Plants that lay within the quadrat were identified, counted and collected for identification, which was carried out by comparison with specialist bibliographies and weed identification manuals. Evaluated variables were: frequency, density, abundance, relative frequency, relative density, relative abundance and species importance value index. In the soybean cultivation area, 60% of the sampled species were Eudicotyledons, and a total of 8 botanical families and 10 weed species were identified. The species Cenchrus echinatus, Ipomoea asarifolia (Desr.) Roem. & Schult, Amaranthus retroflexus L. and Zea mays L showed the highest values for the analyzed variables, and should therefore be of special attention to soybean producers in the region of Vale da Gurguéia, Piauí, Brazil.